2000
DOI: 10.2337/diabetes.49.6.981
|View full text |Cite
|
Sign up to set email alerts
|

High glucose and glucosamine induce insulin resistance via different mechanisms in 3T3-L1 adipocytes.

Abstract: Sustained hyperglycemia induces insulin resistance, but the mechanism is still incompletely understood. Glucosamine (GlcN) has been extensively used to model the role of the hexosamine synthesis pathway (HSP) in glucose-induced insulin resistance. 3T3-L1 adipocytes were preincubated for 18 h in media ± 0.6 nmol/l insulin containing either low glucose (5 mmol/l), low glucose plus GlcN (0.1-2.5 mmol/l), or high glucose (25 mmol/l). Basal and acute insulin-stimulated (100 nmol/l) glucose transport was measured af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
125
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 56 publications
(67 reference statements)
18
125
1
Order By: Relevance
“…In addition, no significant difference in the glucose uptake was detected when the hyperglycemic effect of long-term (24 h) vs short-term (0.5 h) incubation was examined (Figure 1). These results are consistent with recent studies reporting that high glucose treatment alone did not impair insulin-induced glucose uptake in adipocytes and skeletal muscle (Nelson et al, 2000;Kawanaka et al, 2001). However, an experimental condition of high glucose (25 mM) plus high insulin (100 nM) for 24 h exposure, demonstrated to produce insulin resistance in L6 myoblasts and 3T3-L1 adipocytes (Thomson et al, 1997;Tong et al, 2001), significantly decreased the insulinstimulated glucose uptake in H9c2 cells (Figure 2).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, no significant difference in the glucose uptake was detected when the hyperglycemic effect of long-term (24 h) vs short-term (0.5 h) incubation was examined (Figure 1). These results are consistent with recent studies reporting that high glucose treatment alone did not impair insulin-induced glucose uptake in adipocytes and skeletal muscle (Nelson et al, 2000;Kawanaka et al, 2001). However, an experimental condition of high glucose (25 mM) plus high insulin (100 nM) for 24 h exposure, demonstrated to produce insulin resistance in L6 myoblasts and 3T3-L1 adipocytes (Thomson et al, 1997;Tong et al, 2001), significantly decreased the insulinstimulated glucose uptake in H9c2 cells (Figure 2).…”
Section: Discussionsupporting
confidence: 93%
“…This result is consistent with recent findings (Nelson et al, 2000;Kawanaka et al, 2001) demonstrating that high glucose treatment alone does not impair insulin-induced glucose uptake in adipocyte and muscle. …”
Section: R Esultssupporting
confidence: 94%
“…This finding is consistent with studies showing that glucosamine-or hyperglycemia-induced insulin resistance is not associated with insulin receptor or IRS tyrosine phosphorylation defects (33,57). Although it has been suggested that HSPmediated insulin resistance is associated with reduced GLUT4 expression (38), Buse and colleagues (55) found that HSPmediated insulin resistance at physiological levels of chronic insulin is not associated with reduced GLUT4 levels. Similarly, we found that PUGNAc has no effect on the expression level of GLUT4 (Fig.…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have concluded that GlcN and glucose induce insulin resistance by different mechanisms in 3T3-L1 adipocytes and in rat skeletal muscle (32)(33)(34). Rather than postulating differences in mechanisms of action, we believe that GlcN can mimic hyperglycemic conditions by rapidly increasing flux through the HBP resulting in elevated levels of UDP-GlcNAc and increased O-linked glycosylation of regulatory proteins.…”
Section: Discussionmentioning
confidence: 99%